Access and modulation of substituted 1-methyl-1, 6-dihydropyrazolo[3, 4-c]pyrazoles. Issue 16 (5th March 2021) - Ostache, Nicu-Cosmin; Hiebel, Marie-Aude; Fînaru, Adriana-Luminiţa; Allouchi, Hassan; Guillaumet, Gérald; Suzenet, Franck
Abstract : A convenient design of pyrazolo[3, 4- c ]pyrazoles is reported through hydrazine condensations and C–N Ullmann-type cross-coupling reactions. Chemoselective bromination followed by Suzuki–Miyaura cross-coupling reactions access to a variety of modulated heterobicycles. Abstract : Despite the pharmacological potential of the pyrazolo[3, 4- c ]pyrazoles, only a few methods of preparation and direct functionalization of this moiety have been described. We report herein a convenient design of new pyrazolo[3, 4- c ]pyrazoles with a high therapeutic impact. The effective chosen strategy consists of hydrazine condensations and C–N Ullmann-type cross-coupling reactions with microwave activation. Moreover, chemoselective bromination of the newly formed bipyrazoles followed by Suzuki–Miyaura cross-coupling reactions allowed the synthesis of a variety of modulated heterobicycles.